Strategic Feeding of Ammonium and Metal Ions for Enhanced GLA-Rich Lipid Accumulation in Cunninghamella bainieri 2A1 - Shuwahida Shuib; Wan Nazatul Naziah Wan Nawi; Ekhlass M. Taha; Othman Omar; Abdul Jalil Abdul Kader; Mohd Sahaid Kalil; Aidil Abdul Hamid (The Scientific World Journal)
Strategic feeding of ammonium and metal ions (Mg2+, Mn2+, Fe3+, Cu2+, Ca2+, Co2+, and Zn2+) for enhanced GLA-rich lipid accumulation in C. bainieri 2A1 was established. When cultivated in nitrogen-limited medium, the fungus produced up to 30% lipid (g/g biomass) with 12.9% (g/g lipid) GLA. However, the accumulation of lipid stopped at 48 hours of cultivation although glucose was abundant. This event occurred in parallel to the diminishing activity of malic enzyme (ME), fatty acid synthase (FAS), and ATP citrate lyase (ACL) as well as the depletion of metal ions in the medium. Reinstatement of the enzymes activities was achieved by feeding of ammonium tartrate, but no increment in the lipid content was observed. However, increment in lipid content from 32% to 50% (g/g biomass) with 13.2% GLA was achieved when simultaneous feeding of ammonium, glucose, and metal ions was carried out. This showed that the cessation of lipid accumulation was caused by diminishing activities of the enzymes as well as depletion of the metal ions in the medium. Therefore, strategic feeding of ammonium and metal ions successfully reinstated enzymes activities and enhanced GLA-rich lipid accumulation in C. bainieri 2A1.